Perancangan Aplikasi Arah Kiblat dan Jadwal Waktu Shalat Berbasis Android AQ-Shalat - Sunardi Sunardi; Abdul Fadlil; Muhammad Nashiruddin Darajat (University of Muhammadiyah Sumatera Utara, 2021)
The five daily prayers are an obligation that must be carried out by Muslims every day. Carrying out in accordance with the times that have been determined and facing the Qibla is a virtue in carrying out this obligatory worship. Of course, in this modern era, Muslims should not use their busy lives as an excuse to neglect the command to pray. Therefore, Muslims need to be disciplined in dividing their time. The use of mobile devices as a companion in carrying out daily activities is very common for some people. This is because some cellphones already have more functions and capabilities than just their basic functions. Android as an operating system that can be embedded in mobile devices has the ability to install applications needed by users. In this final project, a prayer application and Qibla direction are developed, it is hoped that Muslims who use mobile devices based on the Android operating system can be helped to continue to carry out worship on time and in accordance with the correct Qibla direction.